Corrosion resistance of alloys of Hastelloy in chloroaluminate melts - V. V. Karpov; A. V. Bazhenov; A. V. Abramov; I. B. Polovov; O. I. Rebrin (Chimica Techno Acta)
The corrosion of Hastelloy S, Hastelloy X, Haynes 230, Hastelloy N, Hastelloy G35 and Hastelloy C2000 alloys was studied in KCl–AlCl3 melts at 550 °С. The rates and the mechanisms of corrosion of the studied materials were determined. The processes taking place during the interaction between alloys and chloroaluminate melts were investigated.